GRAZING INTENSITIES OVER IMPROVED NATURAL PASTURE - SOARES, André Brugnara; SARTOR, Laércio Ricardo; MEZZALIRA, Jean Carlos; ADAMI, Paulo Fernando; FONSECA, Lidiane; MIGLIORINI, Francisco; ASSMANN, Tangriani Simioni (Scientia Agraria, 2007)
This essay was conducted over an improved native pasture with the introduction of exotics species (white clover, red clover and birdsfoot trefoil) plus fertilization and lime application in Água Doce-SC, between June of 2004 and May of 2005. The aim of the evaluations was to determinate the influence of two grazing intensities over the animal production. The treatments were composed of two intended forage mass (FM): 2000 e 1000 kg of Dry Matter (DM) ha-1, for the High Mass (HM) and Low Mass (LM) under continuous grazing with variable stocking rate. However, the real FM values were 1875 and 988 kg of DM ha-1 for HM and LM (P<0.05), respectively. The average Herbage Allowance (HA) was 27 and 10 kg of DM 100 kg-1 of PV for HM e LM (P<0.05), respectively. There was no significantly interaction between treatments and periods (P>0.05) for Stocking Rate (SR), the values were 309 and 484 kg of Live Weight (LW) ha-1 for HM e LM, respectively. There was significant interaction between the treatment and period (P<0.05) for Average Weight Daily Gain (AWDG), the values were 0.346 and 0.217 kg day-1 for HM and LM, respectively. There was a significant interaction between treatment and period (P<0.05) for animal production per area, the values were 174 and 254 kg of LW ha-1 for HM and LM, respectively. It can be concluded the grazing intensities influence the animal production in improved native pasture.